Transient acute tubular dysfunction in the newborn: CT findings - McLaughlin, M G; Swayne, L C; Rubenstein, J B; Schwartz, J R; Block, D C (Pediatric radiology, 1990)
We report the CT and sonographic findings of transient acute tubular disease in a newborn infant, who was dehydrated at birth. The initial CT scan demonstrated focal areas of increased attenuation within the central portions of both kidneys, and sonography showed echogenic medullary pyramids. After adequate hydration, a follow-up examination demonstrated complete spontaneous resolution.